2010
DOI: 10.2343/geochemj.1.0063
|View full text |Cite
|
Sign up to set email alerts
|

Sterol composition of dinoflagellates: Different abundance and composition in heterotrophic species and resting cysts

Abstract: The motile cells of the autotrophic dinoflagellates Peridinium umbonatum var. inaequale, Akashiwo sanguinea, Scrippsiella tinctoria, and Prorocentrum micans commonly contain five major sterols: cholesterol, 4-methylcholestan-3-ol, 4,24-dimethylcholestan-3-ol, dinosterol, and dinostanol. The motile cell of the heterotrophic dinoflagellate Protoperidinium crassipes contains cholesterol, 4,24-dimethylcholestan-3-ol, dinosterol, dinostanol, and 4-tetramethylcholestan-3-ol as major free sterols. The dinosterol conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…The study found that the increase in expression of genes related to cholesterol biosynthesis, whereas cholesterol degradation genes were under-expressed in the bloom sample relative to the surrounding non-bloom samples may be associated to resting cysts' formation. As the accumulation of dinosterols may be indicative of bloom termination as demonstrated by a number of studies, these transcriptome behaviors might indicate that during bloom formation, dinoflagellates synthesize more cholesterol to serve as energy storage during their resting stage [81,82]. To date, the number of studies that employed the metatranscriptomics approach to understand bloom dynamics is still relatively few, suggesting that more study is needed, especially regarding differently-expressed genes during bloom development such as bloom initiation, establishment and termination.…”
Section: Habs Dynamicsmentioning
confidence: 99%
“…The study found that the increase in expression of genes related to cholesterol biosynthesis, whereas cholesterol degradation genes were under-expressed in the bloom sample relative to the surrounding non-bloom samples may be associated to resting cysts' formation. As the accumulation of dinosterols may be indicative of bloom termination as demonstrated by a number of studies, these transcriptome behaviors might indicate that during bloom formation, dinoflagellates synthesize more cholesterol to serve as energy storage during their resting stage [81,82]. To date, the number of studies that employed the metatranscriptomics approach to understand bloom dynamics is still relatively few, suggesting that more study is needed, especially regarding differently-expressed genes during bloom development such as bloom initiation, establishment and termination.…”
Section: Habs Dynamicsmentioning
confidence: 99%
“…Dinoflagellate sterols (also referred to as dinosterols) have been shown to increase during resting cyst formation, possibly for use as long-term organic carbon reserves (Amo et al, 2010). Chemically reduced carbon allocated to the synthesis of cholesterols would then be used to support later growth when environmental conditions are more favorable to proliferate.…”
Section: Molecular Insights Into a Dinoflagellate Bloommentioning
confidence: 99%
“…One of the characteristic features of the Precambrian biomarker records is that eukaryotic steranes are typically absent or occur in very low concentrations. This may be explained by a limited ecological distribution of eukaryotic algae and thus minor contributions of sterols to sedimentary OM (Anbar and Knoll, 2002;Blumenberg et al, 2012;Brocks et al, 2017;Knoll et al, 2007), and/or by a thermal degradation of sterols during catagenesis, as observed for the 1640 Ma Barney Creek Formation and 1430 Ma Velkerri Formation, Northern Territory, Australia (Dutkiewicz et al, 2003;Summons et al, 1988). An alternative explanation would be that eukaryotic lipids have been subject to a preservation bias due to the ubiquity of benthic microbial mats.…”
mentioning
confidence: 99%